Human rights reporting: rights, responsiblities, and challenges - Andreopoulos, George J. (Human rights review, 2018)
This essay critically examines the intersections between news media and human rights in the context of the existing human rights framework. A survey of the fundamental provisions of international human rights law and of the evolving case law of human rights organs relating to media freedom and responsibilities reveals that existing gaps and underspecified obligations render problematic the normative guidance offered by the framework in addressing the pertinent human rights issues. However, this is part of the story. The problems associated with normative guidance are compounded by media practitioners’ contending approaches on the role of the media as “promoters of human rights.” The interplay between these factors is then examined through the prism of the two communities’ converging commitment to “truth-seeking.” This commitment can provide entry points to a more constructive engagement between the news media and the human rights community.